2000
DOI: 10.1029/1999jc000016
|View full text |Cite
|
Sign up to set email alerts
|

Results of the Sea Ice Model Intercomparison Project: Evaluation of sea ice rheology schemes for use in climate simulations

Abstract: Abstract.A

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
106
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(110 citation statements)
references
References 55 publications
2
106
2
Order By: Relevance
“…the viscous-plastic (VP) rheology with an elliptical yield curve and a ratio of major to minor axes, e = 2 [Hibler, 1979], or the ice thickness redistribution due to ridging. In fact, Kreyscher et al [2000] also found that a model with a VP rheology and an elliptical yield curve (e = 2) predicted ice in the Beaufort Sea over 1.5 m thicker than observed. Similarly, Fichefet and Morales Maqueda [1997] found that modeled annually-averaged ice thickness increased by 1.5 m in the Canadian Basin and decreased by similar amounts near the North Pole when shear strength was neglected.…”
Section: Comparing Modeled and Observed Draftmentioning
confidence: 79%
See 1 more Smart Citation
“…the viscous-plastic (VP) rheology with an elliptical yield curve and a ratio of major to minor axes, e = 2 [Hibler, 1979], or the ice thickness redistribution due to ridging. In fact, Kreyscher et al [2000] also found that a model with a VP rheology and an elliptical yield curve (e = 2) predicted ice in the Beaufort Sea over 1.5 m thicker than observed. Similarly, Fichefet and Morales Maqueda [1997] found that modeled annually-averaged ice thickness increased by 1.5 m in the Canadian Basin and decreased by similar amounts near the North Pole when shear strength was neglected.…”
Section: Comparing Modeled and Observed Draftmentioning
confidence: 79%
“…[13] Increasing the shear strength of the ice in the model, so that the ice can withstand more shear stress before deforming plastically, can be accomplished by decreasing the ratio of the elliptical yield curve's major to minor axes, e. The value of e = 2 (solid ellipse in Figure 2) is widely used [Hibler, 1979;Kreyscher et al, 2000;Rothrock et al, 2003;Miller et al, 2005] and was chosen on the basis of comparisons with ice deformation [Hibler, 1975[Hibler, , 1979.…”
Section: Improvements Due To Increased Large Scale Shear Strengthmentioning
confidence: 99%
“…To achieve this, data gathered by manned stations, drifting buoys and lately satellite sensors have been used extensively in pan-Arctic sea-ice model validations (Lemke et al 1997;Kreyscher et al 2000;Martin & Gerdes 2007) and data assimilations (Meier et al 2000;Rollenhagen et al 2009). For remote coastal regions such as the Laptev Sea Shelf, there are very few ice drift field observations available.…”
Section: Introductionmentioning
confidence: 99%
“…All the terms are expressed per unit area of the grid box (not per unit area of ice; Connolley et al, 2004). The ice-ocean stress τ w is parameterised as c w ρ w |u i −u w |(u i −u w ), with c w the ice-ocean drag coefficient (0.0055, Kreyscher et al, 2000), ρ w the density of seawater and u w the surface ocean velocity. EVP was designed to be implemented in a parallel context and scales well, and so is particularly suitable for use in in HadCM3.…”
Section: The Elastic Viscous-plastic Rheologymentioning
confidence: 99%